Optimizing Regional Budget Management through Financial Ratio Analysis - Deasy Eviya Anggraini; Bintang Eko Dwi Prayoga (Al-Qalam Institute, 2024)
This study aims to analyze regional financial performance and regional financial capacity of the City Government. The data analysis in this study is descriptive quantitative by calculating the financial ratios of the Regional Revenue and Expenditure Budget (APBD). These data were obtained through the Notes to the Financial Statements (CaLK) for 2017-2021. The results of this study indicate that the regional financial performance of Surakarta City in 2017-2021 shows the ratio of independence included in the delegative relationship pattern with the highest ratio of independence in 2021 of 102.82%. The rise and fall of the independence ratio is also accompanied by the rise and fall of the dependency ratio in the medium to low category and the ratio of the degree of fiscal decentralization in good condition. The ratio of effectiveness and efficiency ownsource revenue receipts has also fluctuated, but the level of effectiveness has been adjusted effectively to very effective and the efficiency is still focused on being very good or efficient. Regional Government spending is still prioritized for direct spending with a ratio of direct and indirect expenditure of 35.61% to 64.39%. Furthermore, the position of locking the regional financial capacity is in quadrant II, namely low share and high growth with an average share of 45.93% and an average growth of 106.62%. While the results of the calculation of the City Financial Capability Index for Fiscal Years 2017 to 2021, the index scale shows the number 0.938, This means that the Financial Capability is high. The implication of this study is that the City Government has shown good financial performance during the period under investigation, with the independence ratio increasing over time.